2011
DOI: 10.1002/cjg2.1600
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Between Land Surface Temperatures Obtained by Field Measurement and Satellite Remote Sensing and Its Implication in Earthquake Research

Abstract: The satellite thermal infrared remote sensing is attracting more and more attention in earthquake science, for satellite remote sensing has a significant advantage of the space information. However, there exist many key basic problems which should be delt with. For instance, what data should be suitably chosen in earthquake research? In this paper, the relationship between land surface temperatures obtained by field measurement and satellite remote sensing is studied, based on data from March, 2006 to February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A lot of authors (Wang and Zhou, 1984;Gorny et al, 1988;Qiang, Xiu-Deng, and Chang-Gong, 1991;Tronin, 1996;Tramutoli et al, 2001;Ouzounov and Freund, 2004;Choudhury et al, 2006a;Panda et al, 2007;Saraf et al, 2009;Chen et al, 2011, Blackett, Wooster and Malamud, 2011, Guangmeng, 2012Qin et al, 2012;Sulçe, 2013) have found that surface air temperature increases in a close proximity to the future earthquake's epicentre. Other papers report for systematic changes of geomagnetic field prior to earthquakes (EQ) (Hayakawa et al, 1996;Mavrodiev, 2004;Kilifarska, Nedialkov and Velichkova, 2015a).…”
Section: Results Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of authors (Wang and Zhou, 1984;Gorny et al, 1988;Qiang, Xiu-Deng, and Chang-Gong, 1991;Tronin, 1996;Tramutoli et al, 2001;Ouzounov and Freund, 2004;Choudhury et al, 2006a;Panda et al, 2007;Saraf et al, 2009;Chen et al, 2011, Blackett, Wooster and Malamud, 2011, Guangmeng, 2012Qin et al, 2012;Sulçe, 2013) have found that surface air temperature increases in a close proximity to the future earthquake's epicentre. Other papers report for systematic changes of geomagnetic field prior to earthquakes (EQ) (Hayakawa et al, 1996;Mavrodiev, 2004;Kilifarska, Nedialkov and Velichkova, 2015a).…”
Section: Results Of Analysismentioning
confidence: 99%
“…This wave band, however, is highly sensitive to the amount of water vapour in the lower troposphere (Kilifarska, 2012), so the "skin" temperature measured by the satellites could substantially deviates from the ground based temperature measurement. This effect has been noticed by Chinese scientists (Chen et al, 2011), who pay attention that groundbased and satellite measurements of the high frequency fluctuations (with period 10 days or less) of the surface temperature are uncorrelated. For this reason this paper is focused on analysis of ERA-Interim reanalysis, providing two near surface temperaturesthe air temperature at 2 m above the surface and the soil temperature at ~3 m below the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The MODIS (http://modis.gsfc.nasa.gov, accessed on 25 March 2023) is a payload on board the satellite with 36 optical channels, six of which provide detection information related to land surface temperature (LST) [18]. A comparative study of LSTs obtained by field measurements and satellite remote sensing indicated that there was no substantial difference between the results of the dayside and nightside data for the anomaly analysis on a monthly scale [47]. In addition, the environmental disturbances were mostly high-frequency information, and the radiation anomalies associated with major EQs were mostly low-frequency information.…”
Section: Modis Data and Methodsmentioning
confidence: 99%
“…In this manner, Tralli et al (2007) present a conceptual case for the assimilation of InSAR measurements into the HAZUS-MH earthquake module. Based on data from thermal sensors, short-term temperature increases prior to several earthquake events have been described numerous times for both surface and atmosphere (Gorny et al 1988;Tronin 1996;Ouzounov & Freund 2004;Saraf & Choudhury 2005;Ouzounov et al 2006;Choudhury et al 2006;Yurur 2006;Ouzounov et al 2007;Yang & Guo 2010;Saradjian & Akhoondzadeh 2011;Chen et al 2011), what may hold information for earthquake prediction and warning (see also Saraf et al (2009) for a discussion of reasons of correlation of these phenomena). Also, other anomalies related to earthquakes that can be detected by remote sensing instruments are discussed in the literature (Tronin 2010) such as ionospheric (Kakinami et al 2010) or cloud (Gup & Xie 2007) anomalies.…”
Section: Pre-eventmentioning
confidence: 99%